Untouchable Fictions : Literary Realism and the Crisis of Caste - Gajarawala, Toral Jatin (Book collections on Project MUSE., 2013)
This title considers the crisis of literary realism - progressive, rural, regionalist, experimental - in order to derive a literary genealogy for the recent explosion of Dalit ('untouchable caste') fiction.